Online Costumer Reviews (OTRs) dan Rating: Kekuatan Baru pada Pemasaran Online di Indonesia - Zakky Fahma Auliya; Moh Rifqi Khairul Umam; Septi Kurnia Prastiwi (EBBANK, 2017)
The background of this research was  gap research between Nieto et al (Nieto, Hernández-Maestro, & Muñoz-Gallego, 2014) with Wang et al (Wang, Liu, & Fang, 2015). This research added intervening variable namely customer perseption to express customer reviews online and rating on purchase decisions in the Indonesia marketplace by using purposive sampling technique approach. The sample is 100 people in Surakarta that had made a purchase online in the marketplace. Customer reviews online and rating in this study are expected to affect purchasing decisions of online product on the marketplace. By using analytical tools AMOS 21, we found that customer reviews online has a positive and significant effect on the customer perception. Rating is also has positive and significant effect on the customer perception. The results of this study also revealed that the customer perception has positive and significant effect on purchasing decisions.